2017
DOI: 10.1080/10962247.2017.1314871
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of atmospheric mercury concentrations emitted from a coal-fired power plant in Mexico

Abstract: The obtained concentrations of mercury from a bigger coal-fired plant in Mexico, through the application of the CALPUFF dispersion model by the mercury emissions, are below the level recommended according to the US Department of Health and Human Services and Integrated Risk Information System. These results provide evidence of important progress in the planning and installation to the future of monitoring mercury stations in the area of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…To estimate mercury mass balance in CETEPEC it was necessary to consider the mercury concentration in coal (0.335 mg/kg), mercury concentration in bottom ash and slag (0.148 mg/kg), and mercury concentration in fly ash (0.017 mg/kg), all of them analyzed by Fuentes et al (2017). CETEPEC consumed 5 832 666 t of coal in 2013, 10 % (583 266 t) corresponding to bottom ash and slag, and fly ash.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To estimate mercury mass balance in CETEPEC it was necessary to consider the mercury concentration in coal (0.335 mg/kg), mercury concentration in bottom ash and slag (0.148 mg/kg), and mercury concentration in fly ash (0.017 mg/kg), all of them analyzed by Fuentes et al (2017). CETEPEC consumed 5 832 666 t of coal in 2013, 10 % (583 266 t) corresponding to bottom ash and slag, and fly ash.…”
Section: Resultsmentioning
confidence: 99%
“…(1) because mercury concentration is different in the coal used by coalfired power plants. To determine the mercury emission, we used a concentration of 0.335 mg Hg/kg of coal, determined by Fuentes et al (2017) for Mexico.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation shown that Hg pollution areas match well with the location of the expressway, peri-urban, rural settlement and quarries. Previous studies reveal that Hg concentrations in surface soils are mainly attributed atmospheric deposition [60][61][62][63]. The results of the air pollution monitor show that the concentration of Hg is relatively high in heavily polluted areas (Unpublished data).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Natural sources include volcanoes, geothermal activity, geological deposits of Hg minerals and re-emission of Hg previously deposited from air onto the surface of soil and water, whereas anthropogenic sources derive from mining (both for Hg and for other minerals) and extraction and burning of fossil fuels, which contain Hg as a trace contaminant (primarily coal), as well as production of metals, alkalis, cement and waste incineration [ 7 , 8 ]. Among industrial activities, GEM emission is prevalent especially at mining sites [ 9 , 10 , 11 , 12 ] and chlor-alkali plants using Hg-cell technology [ 13 , 14 , 15 ], but also in other Hg-related factories [ 16 , 17 , 18 ]. The atmosphere is the central pathway of dispersion for Hg emissions.…”
Section: Introductionmentioning
confidence: 99%